International Market Development Strategy in Companies - Riyanto, Slamet; Sudarso, Satrio; Sumardi, Sumardi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In the era of globalization, international market development is an important strategy for companies that want to expand their business reach and increase their competitiveness in the global market. This article discusses various strategies that companies can implement in developing international markets, from market research to technological innovation. Comprehensive market research, SWOT analysis, and a deep understanding of local consumer preferences are crucial first steps. In addition, customization of products and services, strategic alliances with local companies, and segmented marketing strategies are key elements in ensuring success in international markets. Compliance with trade regulations and policies is also very important to avoid legal problems and ensure smooth business operations. Through a proactive approach and investment in training and technology, companies can overcome legal and operational obstacles, strengthen their reputation, and achieve sustainable growth in the global marketplace.